The Role of Co-Creation in Visual Strategies for Social Campaigns on Food Waste Issues on Instagram: A Case Study of Foodcycle Indonesia - Nabila Widjayanti Utomo; Riky Azharyandi Siswanto; Wirania Swasty (Eduvest - Journal of Universal Studies, 2026)
Food waste is a significant issue in Indonesia affecting social, economic, and environmental sectors, requiring active public participation to address it. Although social media is widely used by organizations to raise awareness, audience engagement remains relatively low. This research aims to analyze the factors influencing audience engagement in FoodCycle Indonesia’s Instagram campaigns and develop a visual campaign strategy based on a co-creation approach. This research uses a mixed method approach with quantitative data collection through questionnaires to 166 Instagram audience respondents, as well as qualitative data through semi-structured interviews, Instagram content observation, and a co-creation process involving 10 selected participants. Quantitative data was analyzed descriptively, while qualitative data was analyzed using Miles and Huberman's interactive analysis model. The results show that even though the audience is interested in the issue of food waste and finds the FoodCycle Indonesia campaign message relatively clear, the level of audience interaction with the content is still moderate. Qualitative findings reveal a gap between the campaign's informative visual strategy and the audience's preference for more relevant, participatory, and contextual content. Through a co-creation approach, the audience is actively involved in the campaign's visual design process, resulting in content concepts that are more in line with the audience's needs and expectations. This study contributes by showing that the co-creation approach can be a relevant strategy in increasing audience engagement in social campaigns on social media, especially in the context of food waste issues in Indonesia.